Impact of Longshore Currents and Wave Energy on Estuary Morphodynamics: A Case Study of Selagan Jaya Beach: Pengaruh Arus Pantai Panjang dan Energi Gelombang terhadap Morfodinamika Muara: Studi Kasus Pantai Selagan Jaya - Elmiati Elmiati; Supiyati Supiyati; Suwarsono Suwarsono (Universitas Muhammadiyah Sidoarjo, 2023)
Estuarine morphology is profoundly influenced by dynamic coastal processes, particularly the interplay of longshore currents and wave energy. This study delves into the evolving Selagan Jaya River estuary, characterized by changing mouth morphology attributed to siltation. Longshore currents and wave energy, stemming from coastal waters, play a pivotal role in this transformation. Employing field measurements encompassing current direction, speed, wave height, period, and drone-aided visualizations at five strategic points, a comprehensive analysis was conducted. Quantitative findings reveal wave heights ranging from 0.01 to 1.74 m, wave periods spanning 3 to 11 s, and current speeds oscillating between 0.1 to 1.1 m/s in a westerly direction. The outcomes unequivocally underscore the significant influence of longshore currents and wave energy on estuarine evolution, specifically in shaping the Selagan Jaya Estuary through sedimentation-induced siltation. These findings bear implications for coastal management and morphological preservation in estuarine environments worldwide. Highlight: Dynamic Influence: This study emphasizes the substantial impact of longshore currents and wave energy on the morphology of evolving estuarine systems. Changing Estuary Shape: The research focuses on the Selagan Jaya River estuary, illustrating how dynamic coastal processes, particularly sedimentation-driven siltation, contribute to alterations in mouth morphology. Comprehensive Analysis: Through field measurements and drone-assisted visualizations, the study provides quantitative insights into wave characteristics and current dynamics, revealing the intricate interplay driving estuarine transformation. Keyword: Estuarine Morphology, Longshore Currents, Wave Energy, Coastal Processes, Sedimentation